A Dialectical View on Conduction: Reasons, Warrants, and Normal Suasory Inclinations - Yu, Shiyang; Zenker, Frank (Informal Logic)

(untitled) (Informal Logic, 2019)
When Carl Wellman (1971) introduced the reasoning-type conduction, he endorsed a dialectical view on natural language argumentation. Contemporary scholarship, by contrast, treats conductive argument predominantly on a product view. Not only did Wellman’s reasons for a dialectical view thus fall into disregard; a product-treatment of conduction also flouts the standard semantics of ‘argument’. Attempting to resolve these difficulties, our paper traces Wellman’s preference for a dialectical view to the role of defeasible warrants. These act as stand-ins for (parts of) value hierarchies that arguers of normal suasory inclination find acceptable. We also improve on extant ways of diagramming conduction and distinguish two of its structural variants.